ANALISIS KELAYAKAN USAHA KEDAI KOPI DI KECAMATAN PRAYA KABUPATEN LOMBOK TENGAH - Nurin, Arum Permata; Amiruddin, Amiruddin; Siddik, Muhamad (JURNAL AGRIMANSION, 2023)
Coffee is a plantation product that is generally processed into a drink, enjoyed by almost all groups. Along with this, the number of coffee enthusiasts tends to increase, this condition encourages the growth and development of coffee shops operated by people in various regions, giving rise to tight competition between coffee shop entrepreneurs. This research aims to analyze the benefits, feasibility and obstacles of coffee shop businesses in Praya District, Central Lombok Regency. The method used in this research is a descriptive method and data collection uses survey techniques. The unit of analysis is the coffee shop business in Praya District. This research was located in Praya, Prapen and Leneng sub-districts. The respondents in this study were coffee shop entrepreneurs. The selection of respondents was determined using the census method of 11 coffee shop entrepreneurs in Praya District. The results of the research show that the profit obtained in one month from the coffee shop business in Praya District is IDR 4,377,471, the coffee shop business in Praya District is worth running from the R/C value of 1.37 and the profitability value is 37%, and The obstacles faced by coffee shop entrepreneurs in Praya District are technical, management, financial and juridical aspects. Keywords: Eligibility, Coffee Shop, Praya District